Implementation of The Computerized Maintenance Management System (CMMS) In Government Hospital Facility Management Services (FMS) - SALAMIT, NUR NADIA AMIRA; Abdul Wahid, Encik Abdul Zaki (Progress in Engineering Application and Technology, 2021)
Facility Management Services (FMS) is one of the Hospital Support Services (HSS) available in the government hospitals. There are three private companies located in Peninsular Malaysia were granted with the concessions by the Ministry of Health (MoH) to manage FMS in the government hospitals. As dictated in the Concession Agreement (CA), these companies need to established new Management Information System (MIS) which called Asset & Services Information System (ASIS) as their Computerized Maintenance Management System (CMMS). This paper discusses the implementation of the CMMS in government hospital FMS. The purpose of this study is to identify the CMMS designation used by FM staffs in government hospital FMS and to determine the effectiveness and the challenges of the implementation of this system. There are 150 set of online survey were distributed to the all staffs whom also the CMMS users in the 3 HSS providers and interview sessions was also conducted. The Cronbach’s Alpha test and Descriptive Analysis was conducted in order to measure the reliability of the survey form and to provide essential analysis on the CMMS designation and implementation. The survey proven to be reliable. Also, the Work Order Tracking is the most effective aspect while Concerns about Cyber-Security is the greatest challenge of executing CMMS. These 2 aspects was found highly affected by the CMMS Designation.